Toward the Impact of EFL Teachers' Self-Efficacy and Collective Efficacy on Students' Engagement - Lu, Qiaoqiao; Mustafa, Zarina (Frontiers in Psychology, 2021)
Given the centrality of students’ engagement in their academic success, considerable attention has been paid to this construct and its potential predictors. Notwithstanding, a limited number of studies have focused on the role of teacher self- and collective efficacy as antecedents of student engagement. Further, no review study has been carried out to illustrate the impact of teacher efficacy on learning engagement. Hence, the current study intends to review the previous studies conducted on this topic to probe into the beneficial effects of teachers’ sense of efficacy on students’ academic engagement. The predictability power of teachers’ self- and collective efficacy was confirmed through empirical and theoretical evidence. The conclusion and pedagogical implications of the finding are also discussed.